Metagenomic Analysis Reveals Microbial Interactions at the Biocathode of a Bioelectrochemical System Capable of Simultaneous Trichloroethylene and Cr(VI) Reduction - Matturro, Bruna; Zeppilli, Marco; Lai, Agnese; Majone, Mauro; Rossetti, Simona (Frontiers in Microbiology, 2021)
Bioelectrochemical systems (BES) are attractive and versatile options for the bioremediation of organic or inorganic pollutants, including trichloroethylene (TCE) and Cr(VI), often found as co-contaminants in the environment. The elucidation of the microbial players' role in the bioelectroremediation processes for treating multicontaminated groundwater is still a research need that attracts scientific interest. In this study, 16S rRNA gene amplicon sequencing and whole shotgun metagenomics revealed the leading microbial players and the primary metabolic interactions occurring in the biofilm growing at the biocathode where TCE reductive dechlorination, hydrogenotrophic methanogenesis, and Cr(VI) reduction occurred. The presence of Cr(VI) did not negatively affect the TCE degradation, as evidenced by the reductive dechlorination rates estimated during the reactor operation with TCE (111 ± 2 µeq/Ld) and TCE/Cr(VI) (146 ± 2 µeq/Ld). Accordingly, Dehalococcoides mccartyi, the primary biomarker of the reductive dechlorination process, was found on the biocathode treating both TCE (7.82E+04 + 2.9E+04 16S rRNA gene copies g-1 graphite) and TCE/Cr(VI) (3.2E+07 + 2.37E+0716S rRNA gene copies g-1 graphite) contamination. The metagenomic analysis revealed a selected microbial consortium on the TCE/Cr(VI) biocathode. D. mccartyi was the sole dechlorinating microbe with H2 uptake as the only electron supply mechanism, suggesting that electroactivity is not a property of this microorganism. Methanobrevibacter arboriphilus and Methanobacterium formicicum also colonized the biocathode as H2 consumers for the CH4 production and cofactor suppliers for D. mccartyi cobalamin biosynthesis. Interestingly, M. formicicum also harbours gene-complexes involved in the Cr(VI) reduction through extracellular and intracellular mechanisms.